6.7k views
0 votes
Factored form of 2x^2+x-3​

User Obiii
by
5.7k points

2 Answers

5 votes

The correct answer is(2times and plz 3)(x-1)

Step by step explanation

(2*+3)(x-1)= two times to the power of 2-2 times +3 times minus three equals Two times to the power of 2+ X -3

User Fesler
by
4.9k points
3 votes

Answer:

The factored form ⇒ (2x + 3)(x - 1)

Explanation:

2x² + x - 3 = (2x + 3)(x - 1)

2x² = 2x × x

-3 = 3 × -1

First bracket is (2x + 3)

Second bracket is (x - 1)

Check Answer:

(2x + 3)(x - 1) = 2x² - 2x + 3x - 3 = 2x² + x - 3

User FrankieTheKneeMan
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.